DIGITAL-BASED ADMINISTRATIVE GOVERNANCE MENTORING FOR ACHIEVING EFFECTIVE SCHOOLS IN EARLY CHILDHOOD EDUCATION, KINDERGARTEN AND ELEMENTARY SCHOOL UNITS - Ahmad Matinul Haq; Dwi Nur Nikmah; Sri Kurnia Abdi Pradhana; Zachirul Aisyi Al Isyari; Nurul Asrofil Laila; Nurul Farisah (LPPM Universitas Flores, 2026)
Orderly administrative governance is a foundation for building effective schools, yet it remains a challenge for many educational units in rural areas. This community service program aimed to strengthen human resource capacity and organize administration at Early Childhood Education Muslimat NU, Kindergarten Wijaya Kusuma, and SDN Sumengko in Sumengko Village, Kedungpring District, Lamongan Regency, which still faced manual administration, lack of standardization, and minimal digitalization. The program was conducted from February to May 2026 through six stages: preparation, training (40 hours), technology adoption, offline and online mentoring, monitoring, and evaluation. The instruments used included knowledge tests (pre-test and post-test), administrative completeness supervision sheets, questionnaires, and focus group discussions. Data were analyzed using descriptive percentages and N-gain. The results showed that the average participant understanding increased from 45.5 to 83.4 (N-gain = 0.70; high category). Administrative completeness increased from 48% to 87%, while administrative digitalization evolved from a manual system to a structured digital system through the implementation of a spreadsheet-based Effective-School Administrative Governance System comprising 15 modules. The program also produced standardized administrative documents, supervision instruments, a KPI dashboard, and Quality Improvement Teams in each educational unit. It was concluded that digital-based administrative governance mentoring effectively improved human resource competence and administrative completeness while supporting the realization of more effective schools. Program sustainability is directed through periodic mentoring, training of trainers, the development of administrative standard operating procedures (SOPs), and the expansion of the model to other educational units in the surrounding area.